HISTOMORPHOLOGICAL STUDY OF ADRENAL GLAND IN LOCAL ADULT FEMALE DUCK (ANASPLATYHYNCHOS) - Jafar G. A. Al-Jebori; Ahmed O.Hossain; Zina Sh. M. Al-tamimi; Ali K.H. Al-Jebori (Basrah Journal of Veterinary Research)
The study was designed to describe the morphological and histological characteristics of the adrenal gland in female Duck (Anasplatyrhynchos).Ten adrenal glands was used in the study collected from five adult female ducks.The morphological features of glands were described and histological sections were prepared from each sample. The study revealed that theducks have paired glands located in the abdominal cavity at the anterior end of the kidneys.The shape of right gland is semi-circular while, the left elongated or triangular in shape. The mean weight of right gland of duck about (0.39) gram while, the left was (0.41)gram. The mean values of long axis of left adrenal gland about (15.46) mm and the diameter of right gave mean values about (11.30) mm. The histological sections of the adrenal gland revealed in a division of gland into a subcapsular layer (SZ)-(peripheral zone) and central zone (CZ) or inner zone. The subscapular zone (SZ) consisted of groups of cells immediately below the capsule which forms irregularly arranged cords while, there are two types of cells in central zone of gland, the first type of cells, acidophilic cells and the second type of cells, basophilic cells called chromaffin cells.